Development of the University of the Philippines Mindanao integrated information management system developing equipment and semi-expandable supply management subsystem - Gales, Alfredo P. (2010)
This special problem developed a system that focused on the data management for equipment and semi-expendable supplies acquired by the University of the Philippines Mindanao. The Supply and Management Office (SPMO) is responsible for this process. Equipment and semi-expendable supply must be issued with Acknowledgement Receipt for Equipment (ARE). This is in accordance with the guidelines issued by the Commission on Audit (COA). The developed system is composed of two components, offline and online component. The office component name AREHandler is a single-user application developed using JAVA programming language. AREHandler handles; creating new ARE entries, assigning property number and ARE number, updating end users of properties, updating of item condition, and report generation. ESSMS also introduces a new scheme of processing ARE forms. The online component named AREOnline is a multi-user, web-based application created for the end users. A property with a property number and ARE number is issued to a specific end user. AREOnline provides a website for end users where they can easily view the properties currently issued to them. The developed system eliminates the problems encountered by the SPMO with their manual system of data management. AREOnline provides end users a convenient way to monitor the properties issued to them
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: ARE; Data management; Equipment; Property